Protective effect of recombinant interleukin-10 on newborn rat lungs exposed to short-term sublethal hyperoxia - Hyeon-Soo Lee; Young-Joon Ryu; Min-Jae Lee (Clinical and Experimental Pediatrics)
Background Lung injury imposed by hyperoxia is the main cause of bronchopulmonary dysplasia in newborns. These injuries are generated from the early stage of hyperoxia through the main biologic effects of cell death and inflammatory response. Interleukin (IL)-10 is a potent anti-inflammatory cytokine that may have the inhibitory effects on these biologic actions induced by hyperoxia. Purpose Based on our former in vitro studies investigating the effect of recombinant IL-10 (rIL-10) on protecting cultured alveolar type II cells exposed to short-term hyperoxia, we performed the in vivo study to investigate the effect of rIL-10 in newborn rats aged P4 exposed to hyperoxia. Methods Rats were classified into 3 groups; the control group exposed to normoxia for 24 hours; the hyperoxia group exposed to 65% hyperoxia for 24 hours; and the IL10 group treated with intratracheal instillation of rIL-10 prior to exposure to 65% hyperoxia for 24 hours. Following each treatment, the rats were euthanized. Individual lobes of the right lung were prepared for hematoxyling and eosin (H&E) staining and immunohistochemical staining for thyroid transcription factor-1 (TTF1). Bronchoalveolar lavage (BAL) was performed in the left lung to analyze cell counts and cytokines. Results The IL10 group showed preserved air spaces similar to the control group, with decreased cellularity compared to the hyperoxia group, whereas the hyperoxia group showed markedly reduced air spaces with increased cellularity compared to the IL10 group. And, the IL10 group showed more TTF1-positive cells, which represented alveolar type II cells, compared to the hyperoxia group. Inflammatory cells, such as neutrophils and lymphocytes and proinflammatory cytokines of tumor necrosis factor-α, IL-1α, IL-8, and macrophage inflammatory protein-1α were significantly lower in BAL fluid of the IL10 group compared to the hyperoxia group. Conclusion These results indicate that rIL-10 may be a promising pharmaceutical measure for protecting newborn lungs from injury induced at the early stage of hyper oxia.